2004
DOI: 10.1111/j.1540-6040.2005.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Placing Whiteness in Spatial Assimilation Research

Abstract: This paper works through some of the epistemological and methodological consequences of an unreflexive use of white suburbs as the expected residential destination in U.S. spatial assimilation research. Foregrounding immigrant suburbanization in spatial assimilation occludes alternative geographic trajectories; simply put, spatial diffusion need not be central city to suburban decentralization. More problematically, spatial assimilation research often translates residential movement to the suburbs into increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 63 publications
0
76
0
2
Order By: Relevance
“…Residential segregation of immigrants tends to be especially high upon their arrival in the host country Hall 2009;Wright et al 2005). In Sweden, residential segregation is the highest among GS immigrants who are also mainly recent arrivals; they often live in immigrant-dense residential neighborhoods that contain a mix of people from different GS origin countries but very few natives (Åslund et al 2010).…”
Section: Links Between Residential and Workplace Segregationmentioning
confidence: 99%
“…Residential segregation of immigrants tends to be especially high upon their arrival in the host country Hall 2009;Wright et al 2005). In Sweden, residential segregation is the highest among GS immigrants who are also mainly recent arrivals; they often live in immigrant-dense residential neighborhoods that contain a mix of people from different GS origin countries but very few natives (Åslund et al 2010).…”
Section: Links Between Residential and Workplace Segregationmentioning
confidence: 99%
“…In testing aspects of Immigrant Spatial Assimilation Theory, research has generally confirmed the theoretical expectation that residence outside an ethnic concentration is related to increased socioeconomic status, a finding that seems to characterize most Canadian as well as United States places (Allen and Turner, 1996;Alba and Nee, 1999;Alba et al, 2000;Logan et al, 2002;Myles and Hou, 2004;South et al, 2005;Wright et al, 2005;Clark, 2006;Walks and Bourne, 2006). In other words, members of ethnic groups living outside ethnic concentrations tend to have greater educational attainment, better jobs, and/or higher incomes than members of the same groups living within ethnic concentrations.…”
Section: Association Between Residential Concentration and Low Levelsmentioning
confidence: 92%
“…They had the economic resources to choose their residence from a wide range of neighborhoods, but they chose to live in concentrated settlements of their ethnic group rather than disperse into predominantly White areas that had low percentages of Latinos. Wright et al (2005) used a special Census Bureau file not available to most scholars to study eight immigrant nationality groups in Los Angeles. They demonstrated that those group members living in the highest concentrations of their group had lower incomes than those residing in somewhat less concentrated circumstances.…”
Section: Income Levels In Ethnic Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant body of literature that focuses on the specific networks that immigrants create as well as the ways they transform the socioeconomic spaces in cities (Smith 2001;Li 1998;Ley and Murphy 2001;Peach 1996;Wright et al 2005;Light 2006). This study, however, aims to identify the global flows of immigrants to cities around the world.…”
Section: World Cities and Immigrantsmentioning
confidence: 99%